Is Waste Really Dirt? : Some Reflections on Mary Douglas, my iPod, and the Performativity of Partial Understandings - Peeters, Joren (STS Encounters, 2025)
This article argues that it does matter in which terms we understand the alarming material reality of surplus-artefacts polluting our planet, because how we understand these artefacts has an impact on their concrete trajectory and how they are organized. For this, the article proposes to salvage Mary Douglas’ definition of dirt as “matter out of place”. This well-worn understanding of waste lay the foundations of waste and discard studies but is heavily criticized these days. However, contrary to its classic and problematic “symbolic-structuralist” reading, this article argues for a material-semiotic reading of Purity and Danger in which its theory of dirt is not universal, totalizing, and strictly concerned with meaning, but instead situated in concrete empirical exemplars, focussed on the plural processes of socio-technical ordering, and concerned with both meaning, matter and their intrinsic entanglement. Dirt is a specific term that cannot fully capture the complex reality of our contemporary “waste problem”. But this does not mean that the concept is irrelevant in the context of these contemporary environmental challenges. By means of the concrete empirical exemplar of a broken iPod, this article argues that partial understandings of waste indeed do not fully capture the contradictory reality of our contemporary waste problem, but that they nevertheless play an active organizing role in that reality, that they do something. When thinking about our contemporary waste problem, we must thus adjust our theoretical tools: we don’t have to think in terms of adequate or inadequate concepts that capture reality or not, but instead in terms of partial understandings that play a more or less prominent role in organizing reality in a specific way. This idea of the performativity of partial understandings will allow to better think the multiplicity of waste that we actually encounter in practice.